Exact controllability of a semilinear reaction–diffusion equation governed by a bilinear control. Issue 5 (24th March 2023) - Najib, H.; El Ayadi, R.; Ouakrim, Y.; Ouzahra, M.
Abstract : This paper investigates the exact controllability of a semilinear reaction–diffusion equation governed by a multiplicative control. Here, the reaction term leads to an unbounded control operator. We will first study the well-posedness and then proceed to the question of exact steering for the system at hand. Our approaches are based on a fixed point argument and the linearization method. The obtained results are further analysed through a numerical example.